Knowing weather in place: the Helm Wind of Cross Fell - Veale, Lucy; Endfield, G.H.; Naylor, Simon (Elsevier, 2014)
The Helm Wind of Cross Fell, North Pennines, is England's only named wind. As a product of the particular landscape found at Cross Fell, the Helm is a true local wind, and a phenomenon that has come to assume great cultural as well as environmental significance in the region and beyond. In this paper we draw on material from county histories, newspaper archives, and documents relating to investigations of the Helm Wind that were conducted by the Royal Meteorological Society between 1884 and 1889, and by British climatologist Gordon Manley (1908–1980), between 1937 and 1939, to document attempts to observe, measure, understand and explain this local wind over a period of 200 years. We show how different ways of knowing the Helm relate to contemporary practices of meteorology, highlighting the shifts that took place in terms of what constituted credible meteorological observation. We also acknowledge the overlapping nature of these ways of knowing and the persistence of multiple testimonies about the Helm and its effects.